2013
DOI: 10.1097/cco.0000000000000005
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus and brain tumor

Abstract: A more precise understanding of the role of HCMV infection in gliomagenesis and GBM pathogenesis could reveal novel therapeutic and preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 41 publications
1
34
0
3
Order By: Relevance
“…We report the induction of a severe hypersensitivity reaction in a patient with GBM enrolled on a clinical trial evaluating the use of autologous DCs pulsed with human cytomegalovirus (CMV) pp65 RNA and co-injected with recombinant GM-CSF (sargramostim) as an adjuvant. CMV antigens have been reported by several groups to be expressed in GBM tumors and we have demonstrated the relevance of CMV pp65 as an immunologic target in GBM tumors (10, 1416). This is our first experience of a severe immunologic reaction in a patient receiving autologous DC vaccination, which occurred despite the patient being on continuous cycles of lymphodepletive and myelosuppressive TMZ.…”
Section: Introductionsupporting
confidence: 62%
“…We report the induction of a severe hypersensitivity reaction in a patient with GBM enrolled on a clinical trial evaluating the use of autologous DCs pulsed with human cytomegalovirus (CMV) pp65 RNA and co-injected with recombinant GM-CSF (sargramostim) as an adjuvant. CMV antigens have been reported by several groups to be expressed in GBM tumors and we have demonstrated the relevance of CMV pp65 as an immunologic target in GBM tumors (10, 1416). This is our first experience of a severe immunologic reaction in a patient receiving autologous DC vaccination, which occurred despite the patient being on continuous cycles of lymphodepletive and myelosuppressive TMZ.…”
Section: Introductionsupporting
confidence: 62%
“…Remarkably, a recent analysis of monozygotic twin pairs revealed that CMV infection was the primary factor driving nonheritable diversity in the immune system (2). Consistent with the dramatic impact of CMV on the host immune system, infection has been associated with multiple chronic inflammatory conditions, including high blood pressure, heart disease/atherosclerosis, cancer, and aging-related immunodeficiencies (3,4). Despite the clinical importance of human CMV (HCMV), there is currently no vaccine, and antiviral drugs are relatively toxic and cannot restrict viral persistence/latency.…”
mentioning
confidence: 92%
“…More interestingly, HCMV also replicates in neural cells of glia, immature neurons, and neural progenitor/stem cells (NPCs), as well as in glioblastoma and neuroblastoma cell lines (5)(6)(7)(8)(9). Increasingly, observational studies have indicated that HCMV is associated with glioblastoma (10)(11)(12)(13), and recent reports find that this virus establishes persistent/latent infection in T98G glioblastoma cells (14,15). The brain and auditory system (16)(17)(18) are the end-organ sites where damage manifests as sensorineural hearing loss (SNHL), mental retardation, and developmental delays (3,(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%